2011
DOI: 10.1371/journal.pone.0028992
|View full text |Cite
|
Sign up to set email alerts
|

A Model System for In Vitro Studies of Bank Vole Borne Viruses

Abstract: The bank vole (Myodes glareolus) is a common small mammal in Europe and a natural host for several important emerging zoonotic viruses, e.g. Puumala hantavirus (PUUV) that causes hemorrhagic fever with renal syndrome (HFRS). Hantaviruses are known to interfere with several signaling pathways in infected human cells, and HFRS is considered an immune-mediated disease. There is no in vitro-model available for infectious experiments in bank vole cells, nor tools for analyses of bank vole immune activation and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…Similar studies have been performed using bank vole cells infected with PUUV [78]. Embryonic fibroblasts inoculated with PUUV did not express increased amounts of Ifnβ or Mx2 , although non-related viruses were able to induce up-regulation of these genes.…”
Section: Immune Responses Of Rodent Reservoirssupporting
confidence: 67%
“…Similar studies have been performed using bank vole cells infected with PUUV [78]. Embryonic fibroblasts inoculated with PUUV did not express increased amounts of Ifnβ or Mx2 , although non-related viruses were able to induce up-regulation of these genes.…”
Section: Immune Responses Of Rodent Reservoirssupporting
confidence: 67%
“…SEOV infection does not trigger antiviral or proinflammatory responses but suppresses the ability of these BM-derived APCs to respond appropriately to inflammatory stimuli (2). Embryonic fibroblasts from bank voles also do not increase Ifn␤ or Mx2 mRNA expression when infected with the species-specific hantavirus Puumala virus (PUUV) (70). In contrast to reservoir host-derived cells, pathogenic hantavirus infection of human endothelial cells or DCs induces antiviral cytokine (i.e., Ifn␤) and chemokine (i.e., Ccl5 and Cxcl10) expression and increases cell surface activation markers (i.e., MHC-I and ICAM-1) that contribute to the enhanced proinflammatory response and CD8 ϩ T cell activity in HFRS and HCPS patients (30,40,62,71).…”
Section: Discussionmentioning
confidence: 99%
“…This probably reflects the presence of macrophages constitutively expressing the Tnfa gene (Hutchinson et al, 1998;Herbst et al, 2002). Similarly, Stoltz et al (2011) showed that PUUV did not induce an increase in Mx2 mRNA production in bank vole embryonic fibroblasts. The relation observed in this study therefore does not result from differences in the duration since infection between bank voles.…”
Section: Association Between the Expression Of Tnf-a Or Mx2 And Puuv mentioning
confidence: 89%